Dexmedetomidine expands monocytic myeloid-derived suppressor cells and promotes tumour metastasis after lung cancer surgery - Xiaosan Su; Yaodong Fan; Liu Yang; Jie Huang; Fei Qiao; Yu Fang; Jun Wang (Journal of Translational Medicine, 2018)
Abstract Background Dexmedetomidine (DEX) has been reported to promote tumour metastases. However the underlying mechanisms remain unclear. The purpose of this study was to investigate whether DEX promotes tumour metastasis by inducing myeloid-derived suppressor cells (MDSC) in the context of surgery. Methods DEX was given to lung cancer patients and its effects on expansion of monocytic MDSC (M-MDSC) were studied in the context of surgery. Spontaneous tumour metastasis was induced in C57BL/6 mice and the effects of DEX on M-MDSC expansion and metastasis formation were assessed. Results DEX increased CD11b+CD33+HLA-DR–CD14+ M-MDSC in lung cancer patients after thoractomy. DEX-induced M-MDSC, in addition to have immunosuppressive activity, were more efficient in producing VEGF. Expansion of M-MDSC by DEX involved α2-adrenergic receptor. Using an experimental tumour metastasis mouse model, we demonstrated that the numbers of metastases on lung surface and CD11b+Ly6ChighLy6G− M-MDSC during postoperative period were enhanced in DEX-treated mice. Promotion of tumour metastasis by DEX-induced M-MDSC involved VEGF, a key factor for tumour angiogenesis. Conclusions DEX induces the proliferation of M-MDSC during postoperative period in lung cancer patients and this cell population is qualified with potent proangiogenic ability. Treatment of mice with DEX expands M-MDSC and promotes tumour metastasis through the increasing production of VEGF.